Answer:
The solution is:
x=3
y=4
Explanation:
We need to solve this system using the substitution method.
2x + 2y = 14
y = 3x - 5
Substitution method involves placing value of x or y from one equation to other equation.
We have:
![2x + 2y = 14--eq(1)\\y = 3x-5 --eq(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/x0bhw22t2vfacpwouqn5174dxktm0fww5t.png)
We will put value of y from equation 2 into equation 1.
![2x + 2y = 14\\Put\:y = 3x - 5\\2x+2(3x-5)=14\\2x+6x-10=14\\8x=14+10\\8x=24\\x=(24)/(8)\\x=3](https://img.qammunity.org/2022/formulas/mathematics/high-school/hutwcs2r12ua7hgjl14q9dsmqdazepor6m.png)
So, we get x =3
Now, put value of x in equation 2 to find value of y
![y = 3x - 5\\Put\:x=3\\y=3(3)-5\\y=9-5\\y=4](https://img.qammunity.org/2022/formulas/mathematics/high-school/id7dmye4emqfpy1htbpc8z9jajabjs0blp.png)
So, we have y = 4
The solution is:
x=3
y=4